Modeling impact of nitrogen carrier and concentration on root substrate pH. (14th September 2017) - Barnes, Jared; Nelson, Paul V.; Hesterberg, Dean; Shi, Wei; Whipker, Brian E.
ABSTRACT: We conducted an experiment to quantify the effects on substrate pH from nitrogen (N) carrier and concentration. We used four concentrations of N (3.5–14 mM) and five fractions of ammonium (NH4 + ) (0–80% NH4 + of total N) that are found in commercially available fertilizers. Fertilizers were applied to fallow 14-cm-diameter pots (1.29 L) filled with a 3 peat:1 perlite (v/v) substrate amended with non-residual powdered calcium carbonate to raise the substrate pH to approximately 6.0. Harvests occurred at 20 and 42 days. Significant effects in the model included main effects of N carrier and N concentration, their squared terms, an interaction effect, and a time × N carrier. The fraction of NH4 + accounted for 45.0% of variation in substrate pH, and N concentration accounted for 1.5% of the total R 2 of 76.7%. Substrate acidification was likely due to the physiological fertilizer effect and nitrification.